Kombinasi hybrid prosthesis dengan precision attachment pada kasus mahkota klinis pendek Hybrid prosthesis combined with precision attachment to overcome clinically short crown - Irene Melina; Soekobagiono Soekobagiono; Harry Laksono (DiscoverSys Inc., 2013)
In the case of losing many teeth and the residual teeth have short clinical crown, design of the denture may hybriddenture. Hybrid denture is a removable partial denture with metal frame which have retention in the form ofprecision attachment. In short clinical crown, placement of crowns and the use of traction can be a problem,because there is no or lack of retention. In the manufacture of hybrid denture with precision attachment retention,using abutment with short clinical crowns is contraindicated. But in some literatures mentioned that the rest of theclinical crown height of not less than 2 mm can still be used as an abutment, but the abutments must be modified,such as making a longer preparation towards cervical edge. In several studies and literature, it is mentioned that toimprove the retention of the crown, the axial wall of abutment must be 4-6Â°. This article is aimed to report the clinical success of using the hybrid denture on abutment teeth which have short clinical crowns in a patient woman